Cerebellar and Cerebral Amyloid Visualized by [18F]flutemetamol PET in Long-Term Hereditary V30M (p.V50M) Transthyretin Amyloidosis Survivors - Uneus, Erica Irene; Wilhelmsson, Christer; Bäckström, David; Anan, Intissar; Wixner, Jonas; Pilebro, Björn; Riklund, Katrine; Ögren, Mattias; Ögreen, Margareta; Axelsson, Jan; Suhr, Ole B.; Sundström, Torbjörn (Frontiers in Neurology, 2022)
Hereditary transthyretin (ATTRv) amyloidosis caused by the V30M (p.V50M) mutation is a fatal, neuropathic systemic amyloidosis. Liver transplantation has prolonged the patients’ survival, and central nervous system (CNS) complications, attributed to amyloid angiopathy caused by CNS synthesis of variant transthyretin have emerged. The aim of the study was to ascertain amyloid deposition within the brain and neurological signs and symptoms in long-term ATTRv amyloidosis survivors. Twenty ATTR V30M patients with symptoms from the CNS and a median disease duration of 16 years (8-25 years) were included in the study. Cognitive and peripheral nervous function were determined for 18 patients. Amyloid brain deposits were examined by [18F]flutemetamol PET/CT. Five Alzheimer’s disease (AD) patients served as positive controls. Sixty percent of the ATTRv patients had a pathological Z-score in cerebellum, compared to only 20% in the AD patients. Seventy-five percent of the patients with transient focal neurological episodes (TFNEs) displayed a pathological uptake only in the cerebellum. An increased cerebellar uptake was related to an early-age of onset of the ATTRv disease. Fifty-five percent of the ATTRv patients had a pathological Z-score in the global cerebral region compared to 100% of the AD patients. Conclusions: Amyloid deposition within the brain after long-standing ATTRv amyloidosis is common, especially in the cerebellum. A cerebellar amyloid uptake profile seems to be related to TFNE symptoms.